PEMBERIAN MIKROORGANISME SELULOLITIK (MOS) DAN PUPUK ANORGANIK PADA PERTUMBUHAN KELAPA SAWIT (Elaeis guineensis Jacq.) DI TBM II - Gusmawartati Gusmawartati; Hapsoh Hapsoh; Warda Putra Dinata Rambe (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2013)
This study aims to find out the influences and interactions of cellulolytic microorganisms providing inorganic fertilizer on the growth of palm oil and determine cellulolytic microorganisms dosage and proper inorganic fertilizer on plant oil palm in immature palm plants phase II. Research was done on plantations PT. Tunggal Perkasa Plantation Air Molek District Pasir Penyu, sub-province Indragiri Hulu Riau Province. Research carried out for 4 months starting in October 2012 to the month of January 2013. Randomized Design Block (RDB) factorial with two factors namely cellulolytic microorganisms and inorganic fertilizer with 3 replications used on this research. Data was analyzed using ANOVA and extended with further experiments on standard 5% DNMRT. Parameters of the observation was numbers of total frond, long fronds (cm), number of leaflets (sheets), hump circumference (cm) and plant height (cm). The results showed the granting cellulolytic microorganisms 20 mL / plants and the provision of fertilizer inorganic 1/4 x dose can be suppress the use of fertilizers of inorganic up to 75% on growth oil palm in immature palm plants.